2008
DOI: 10.1021/jm8000949
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Pentacyclic Triterpenes as Inhibitors of Glycogen Phosphorylase: Synthesis, Structure−Activity Relationships, and X-ray Crystallographic Studies

Abstract: Twenty-five naturally occurring pentacyclic triterpenes, 15 of which were synthesized in this study, were biologically evaluated as inhibitors of rabbit muscle glycogen phosphorylase a (GPa). From SAR studies, the presence of a sugar moiety in triterpene saponins resulted in a markedly decreased activity ( 7, 18- 20) or no activity ( 21, 22). These saponins, however, might find their value as potential natural prodrugs which are much more water-soluble than their corresponding aglycones. To elucidate the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 191 publications
(147 citation statements)
references
References 74 publications
4
141
1
1
Order By: Relevance
“…Substances like asiatate and maslinate, which are structurally similar to ursolate, as well as (S)-3-(1-methylethyl) 4-(2-chlorophenyl)-1,4-dihydro-1-ethyl-2-methylpyridine-3,5,6-tricarboxylate (W1807), 4-[2,4-bis-(3-nitrobenzoylamino)phenoxy]phthalic acid (Novo4j) and 1-(2-chloro-4-fluorobenzoyl)-3-(5-hydroxy-2-methoxy-phenyl)urea (AVE#21), 21 inhibit the enzyme by binding to this allosteric site, which was chosen to carry out the study on the interaction of these compounds with the glycogen phosphorylase in complexes 2QN1 and 2QN2. Other substances structurally similar to ursolate and active against insects according to the literature were also docked to the allosteric site of the enzyme (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Substances like asiatate and maslinate, which are structurally similar to ursolate, as well as (S)-3-(1-methylethyl) 4-(2-chlorophenyl)-1,4-dihydro-1-ethyl-2-methylpyridine-3,5,6-tricarboxylate (W1807), 4-[2,4-bis-(3-nitrobenzoylamino)phenoxy]phthalic acid (Novo4j) and 1-(2-chloro-4-fluorobenzoyl)-3-(5-hydroxy-2-methoxy-phenyl)urea (AVE#21), 21 inhibit the enzyme by binding to this allosteric site, which was chosen to carry out the study on the interaction of these compounds with the glycogen phosphorylase in complexes 2QN1 and 2QN2. Other substances structurally similar to ursolate and active against insects according to the literature were also docked to the allosteric site of the enzyme (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported to exhibits pharmacological activities, such as anti-tumor, anti-viral, anti-HIV and anti-HCV activities [1,2]. Because of its wide biological activities and its potential applications, the extraction, synthesis and biological activity of oleanic acid and its derivatives have attracted much attention [3][4][5][6][7].Inthis paper, we report the crystal structure of the title compound, whose synthetic protocolhas been alreadyreported elsewhere [7]. In the molecule of thetitle compound (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The residue was purified by column chromatography. (16). Prepared from 4 (0.13 g, 0.27 mmol) and 7 (0.10 g, 0.27 mmol) according to General procedure IVa.…”
Section: General Procedures V For O-deacetylationmentioning
confidence: 99%
“…[13][14][15] X-Ray crystallographic studies revealed the molecular basis of their inhibitory effect, demonstrating that pentacyclic triterpenes such as asiatic and maslinic acids bind to GP at the allosteric site. 16 Oleanolic acid (1, OA), ursolic acid (2, UA) and maslinic acid (3,MA) have recently attracted much attention due to their broad biological activities such as protection of the liver against toxic injury, anti-inflammation, anti-HIV, antitumor, antioxidation, anti-hyperglycemia and cardiovascular activities. 17 Inhibitors having the potential to bind to more than one site of an enzyme may be significantly more efficient than those with a single binding group (for some tentatively selected examples of bi-or trivalent enzyme inhibitors see ref.…”
Section: Introductionmentioning
confidence: 99%